FOLLOW-UP SURVEY OF THE SPECIAL UNIT OF PSYCHOLOGICAL ATTENTION AT SUMMA 112 AFTER THE TERRORIST ATTACKS ON 11TH MARCH IN MADRID - Hillers Rodríguez, Rosalía; Rey Bruguera, Mayelin (Anales de Psicología / Annals of Psychology, 2006)
The Special Unit of Psychological Attention at SUMMA 112 carried out a medium-term follow-up survey with a 350 subjects sample three months after the terrorist attacks on 11th March 2004 in Madrid, and the results are presented in this paper. Method: A protocol designed ad hoc by the Unit, and the TOP-8 and TQ scales were administered by telephone. Results: In our sample of 350 individuals (66 percent were women) 53 percent of respondents were victims, 27 percent direct witnesses, and 19 per-cent indirect witnesses of the attacks. During the follow-up 33 percent of the total sample showed Post-traumatic Stress Disorder (66 percent were victims). 32 percent of people who answered the questionnaire received mental assistance one week after the terrorist attacks. A high number of respondents (82 percent) indicated a reduction of their initial symptoms during the survey, those which urged them to call SUMMA 112 emer-gency numbers in the first moments after the attacks. Conclusion: These results show the consequences on people of a traumatic event and the relevance of immediate and close assistance in psychological crisis intervention in order to diminish the negative effects.